China’s Geopolitical Ambitions of the Xi Jinping Era (Economic and Political Thought, 2023)
China under ever growing autocratic rule of Xi Jinping, which has started atthe end of 2012, is presenting many new proposals and visions, both on domesticand international scene. This article describe those initiatives, usuallyless known outside of China, as they are, additionally, hidden in the Chinesecultural code. What is obvious and clear: the old civilization is under rejuvenationand together with it an empire, with its own concepts for itself andthe whole world. This phenomenon and visible assertiveness of the leadershipin Beijing is changing the global balance of power – with relative decline ofthe West, starting from the USA, and growing impact of emerging marketsand the global South, starting from China, and followed by India. After theCOVID-19 pandemic and full-scale Russian aggression in the Ukraine it isa high time to adjust to the new global order, still under creation. The changeis so deep that any return to the past is just impossible. However, only timewill tell what will be the impact of China’s return to the centre of the globalscene.
Keywords: Xi Jinping, China, Power Shift, Chinese global initiatives, Chinese governance, Chinese cultural code, COVID-19